Samegården, konceptmodell - (:unkn) unknown (Chalmers tekniska högskola // Institutionen för arkitektur och samhällsbyggnadsteknik, 2026)
Do you know what is beneath your feet? Are we showing appropriate respect to the layers that make up our land and our history? What does it mean to live on the edge of understanding, external decision making and (in)justice? And how much are we ready to destroy in search of profit? The concept model shows the sought-after iron ore situated underneath the long Sámi history and presence in this land. Samegården is standing right on the edge of the model showing the fact that the building was right by LKAB's previous red line marking the “to be demolished or moved”-area, and also the uncertainty and confusion that have been caused by the line moving back and forth in the last decade.
Samegården, concept model
Keywords: kiruna; sámi; sápmi; indigenous; nordic architecture; hotel; culture centre; museum; exhibition; community; preservation; ornamentation; details; colour; wood; stone; concrete